2022
DOI: 10.3991/ijim.v16i07.28755
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Elderly Use of Digital Technology in Thailand

Abstract: The elderly population is on the rise, globally. It is an age group that should live to their fullest potential to enhance the quality of their life, should be prepared to live life to the fullest in a way that benefits them, their family, and society. The elderly should be able to access digital technology and benefit from it. Therefore, it is necessary to educate the elderly choosing the right kind of digital technology to their quality of life, and protect themselves from cyber threats. This study performs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…'NA' methodology, initiated by the United Nations Development Program (UNDP) in the 1990s, stands as a cornerstone in various research contexts (Chanyawudhiwan et al, 2023;Chimnoy et al, 2023;Choomsri & Chansirisira, 2023). Shea (1997) and Ul Haq (1995) underscore its systematic approach, facilitating the collection of robust data on social, economic, and environmental conditions.…”
Section: How Critical Is a Needs Assessment?mentioning
confidence: 99%
See 2 more Smart Citations
“…'NA' methodology, initiated by the United Nations Development Program (UNDP) in the 1990s, stands as a cornerstone in various research contexts (Chanyawudhiwan et al, 2023;Chimnoy et al, 2023;Choomsri & Chansirisira, 2023). Shea (1997) and Ul Haq (1995) underscore its systematic approach, facilitating the collection of robust data on social, economic, and environmental conditions.…”
Section: How Critical Is a Needs Assessment?mentioning
confidence: 99%
“…Sittisak et al (2022) reported that NAs were instrumental in helping educators develop management skills and competency. Chanyawudhiwan et al (2023) utilized PNImodified to rank the digital competencies of students in Thai open universities. Chimnoy et al (2023) applied these tools to report on teacher management strategies in private elementary schools, while Choomsri and Chansirisira (2023) highlighted educator needs in developing smart schools, emphasizing that staff, management, media use, and supporting technology were key areas of concern.…”
Section: How Critical Is a Needs Assessment?mentioning
confidence: 99%
See 1 more Smart Citation
“…The elderly population of many countries is growing rapidly and requires special attention to form and promote self-care and enhance their Quality of Life. [2][3][4]. In Iran, statistics show that approximately 9% of the 75 million population of the country are over 65 years of age [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers, however, claimed that the language learners required adequate quantity of exposure to that language to reach the ultimate competency level which could be implied as the use of first language (L1) could hinder their second language (L2) learning. Furthermore, implementing the pedagogy of code-switching has been widely acknowledged, yet the world has been changing within no time as the new environment of the code-switching has been environmentally employed virtually instead of the normal face-to-face teaching and learning as today's people have been surrounded by digital media through smart phones [1]. They have been reading and writing in digital format which could allow them to enhance new literate skills and abilities to learn content concepts.…”
Section: Introductionmentioning
confidence: 99%